Unemployment in the Soviet Union: Evidence from the Soviet Interview Project - Gregory, Paul R.; Collier, Irwin L. (American Economic Review, 1988)
[Unemployment statistics are not published by the Soviet government which claims unemployment was "liquidated" in the early 1930s. An unemployment rate for the Soviet urban population during the late 1970s is calculated from a survey of 2793 former Soviet citizens. Unemployment incidence, multiple spells, and unemployment duration by demographic characteristics are compared with U.S. patterns. Similar unemployment rates for Soviet men and women and a positive relation between education and unemployment are found.]